Deep subsurface mine stalactites trap endemic fissure fluid Archaea, Bacteria, and Nematoda possibly originating from ancient seas - Borgonie, Gaëtan; Linage-Alvarez, Borja; Ojo, Abidemi; Shivambu, Steven; Kuloyo, Olukayode; Cason, Errol D.; Maphanga, Sihle; Vermeulen, Jan-G; Litthauer, Derek; Ralston, Colin D.; Onstott, Tullis C.; Sherwood-Lollar, Barbara; et al. (Frontiers in Microbiology, 2015)
Stalactites (CaCO3 and salt) from water seeps are frequently encountered in ceilings of mine tunnels whenever they intersect water-bearing faults or fractures. To determine whether stalactites could be mineralized traps for indigenous fracture water microorganisms, we analyzed stalactites collected from three different mines ranging in depth from 1.3 to 3.1 km. During sampling in Beatrix gold mine (1.4 km beneath the surface), central South Africa, CaCO3 stalactites growing on the mine tunnel ceiling were collected and discovered, in two cases, to contain a living obligate brackish water/marine nematode species, Monhystrella parvella. After sterilization of the outer surface, mineral layers were physically removed from the outside to the interior, the DNA extracted. Based upon 16S and 18S rRNA gene sequencing, Archaea, Bacteria and Eukarya in different combinations were detected for each layer. . Using CT scan and electron microscopy the inner structure of CaCO3 and salt stalactites were analyzed. CaCO3 stalactites show a complex pattern of lamellae carrying bacterially precipitated mineral structures. Nematoda were clearly identified between these layers confirming that bacteria and nematodes live inside the stalactites and not only in the central straw. Salt stalactites exhibit a more uniform internal structure. Surprisingly, several Bacteria showing highest sequence identities to marine Bacteria were identified. This, together with the observation that the nematode M. parvella recovered from Beatrix gold mine stalactite can only survive in a salty environment makes the origin of the deep subsurface colonization enigmatic. The possibility of a Permian origin is discussed. Our results indicate stalactites are suitable for biodiversity recovery and act as natural traps for microorganisms in the fissure water long after the water that formed the stalactite stopped flowing.